2022
DOI: 10.1111/bjd.21670
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of resuming life after immunotherapy and associated survivorship care needs: a qualitative study among patients with metastatic melanoma

Abstract: Background Immune checkpoint inhibitors (ICIs) have significantly improved the overall survival of patients with metastatic melanoma. It is unclear how the growing group of metastatic melanoma survivors resume their lives after treatment, and which needs they have regarding survivorship care (SSC). Objectives To gain an in-depth understanding of metastatic melanoma survivors' experiences of resuming life after ICIs and their associated SSC needs. Methods A qualitative study was conducted among 20 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
4
17
0
Order By: Relevance
“…Similar to a recent study among advanced melanoma patients receiving immunotherapy, we found that social relationships of long-term responders are challenged [22]. Especially those who have been living for many years with an advanced cancer diagnosis experience that the social environment often does not know to what extent a longterm responder is healthy or ill. Others either under-or overestimate the long-term responder.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to a recent study among advanced melanoma patients receiving immunotherapy, we found that social relationships of long-term responders are challenged [22]. Especially those who have been living for many years with an advanced cancer diagnosis experience that the social environment often does not know to what extent a longterm responder is healthy or ill. Others either under-or overestimate the long-term responder.…”
Section: Discussionsupporting
confidence: 86%
“…Especially those who have been living for many years with an advanced cancer diagnosis experience that the social environment often does not know to what extent a longterm responder is healthy or ill. Others either under-or overestimate the long-term responder. For example, when the long-term responder looks healthy, others assume that the person also feels energetic, or when others learn someone has advanced cancer, they become overprotective [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%
“…In this issue of the BJD , Kamminga et al 4 . highlight currently unmet healthcare needs in people treated for metastatic melanoma.…”
mentioning
confidence: 99%
“…In this issue of the BJD, Kamminga et al 4 highlight currently unmet healthcare needs in people treated for metastatic melanoma. As Kamminga et al show, even when treatment is successful, the psychological impact of a health condition can be significant, and it should not be assumed that medical treatment alone will resolve the difficulties associated with the condition.…”
mentioning
confidence: 99%